El profesionalismo de los gimnasios de la ciudad de Riobamba. - Yumisaca Zumba, Aaron David (2023)
This research is focused on determining the level of professionalism of the coaches in the city of Riobamba; through bibliographical research, we have conceptualized what professionalism is and what they are; the characteristics, aptitudes, qualities, and competencies of a sports professional. Through the various concepts raised, the importance of academic preparation in sports professionals is made known as how it affects the development and growth of the city of Riobamba sports society. This research has a qualitative approach; numerical values do not govern it; the data collection system used was the survey; through a series of questions, we determined the level of academic preparation of the city's coaches. Through the applied survey, it was possible to verify the academic and professional preparation of the active coaches; the results obtained are highly relevant since the present investigation serves as a starting point for new training projects and training of sports professionals.